Influence of Information Technology on Internal Control Systems in Tertiary Institutions in Osun State, Nigeria - Adebayo, Aderemi Olalere; Obisesan, Samuel Oladele; Akinola, Amos Olusola (UUM PRESS, 2024)
The study examined how information technology affects internal control systems in tertiary institutions in Osun State. Specific goals were to ascertain whether or not information technology has a significant impact on the internal control systems and internal audit processes of tertiary institutions. A survey research design was chosen. A sample size of 100 respondents participated in the study. This study used the stratified sampling method and a regression technique was used for data analysis. The findings showed that internal control systems and internal audit procedures in tertiary institutions in Osun State were highly influenced by information technology with t= 20.02 P< 0.0 and t= 19.049p strengthened and improved by information technology. The study has recommended that tertiary institutions adopt information technology in order to improve their internal control frameworks. To keep their staff’s necessary skills and knowledge current, the management of tertiary institutions should encourage both on-the-job and off the-job training in information technology. To stop fraud, internal control mechanisms should be put in place. To establish who will be held accountable for violations, tasks must be digitally separated effectively